2008
DOI: 10.3923/pjbs.2008.1634.1637
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of Engine Oil Polluted Soil by the Tropical White Rot Fungus,Lentinus squarrosulus Mont. (Singer)

Abstract: This study was conducted to test the efficacy of an indigenous white rot fungus Lentinus squarrosulus in degrading engine oil in soil. Flasks containing sterilized garden soil (100 g) moistened with 75% distilled water (w/v) were contaminated with engine oil 1, 2.5, 5, 10, 20 and 40% w/w concentrations, inoculated with L. squarrosulus and incubated at room temperature for 90 days. Levels of organic matter, pH, total hydrocarbon and elemental content (C, Cu, Fe, K, N, Ni, Zn and available P) were determined pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 17 publications
2
22
0
Order By: Relevance
“…Hence, the fungus can be employed in decontaminating environment polluted with engine oil. In a similar study, Adenipekun and Isikhuemhen [62] revealed the ability of white rot fungus, L. squarrosulus to improve the nutrient contents of the engine oil contaminated soil and an accumulation of Fe, Zn and Ni to an appreciable extent.…”
Section: Soil Ecosystemmentioning
confidence: 97%
“…Hence, the fungus can be employed in decontaminating environment polluted with engine oil. In a similar study, Adenipekun and Isikhuemhen [62] revealed the ability of white rot fungus, L. squarrosulus to improve the nutrient contents of the engine oil contaminated soil and an accumulation of Fe, Zn and Ni to an appreciable extent.…”
Section: Soil Ecosystemmentioning
confidence: 97%
“…The fruit body, if harvested within 3 days of fruiting, is used as a meat substitute. It was not until recently that research started to emerge on its application in food [2], medicine [3] [4] and bioremediation [5]. Proximate analysis shows that both the cap and stipe are rich in proteins, sugars, fiber, lipids, amino acids, vitamins B, C, and D, and minerals [6].…”
Section: Introductionmentioning
confidence: 99%
“…TPH is lost at 10% level of contamination through consumption, utilization or breakdown of the cutting fluid contaminated soil into simple compound that are not harmful to the environment. There is possibility of fungus degrading TPH at a level of contamination as low as 1% engine oil concentration if the incubation period is elongated (Adenipekun and Isikhuemhen, 2008). The highest cation exchange capacity value was obtained at 10% level of contamination suggest that bioremediation best occurs at this level of contamination.…”
Section: Discussionmentioning
confidence: 94%